INTERNATIONAL HUMAN RESOURCE MANAGEMENT IN CONTEXT INTERNATIONAL INDUSTRIAL RELATIONS: SYSTEMATIC LITERATURE REVIEW - Fora, Yandri; Perkasa, Didin Hikmah (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Abstract This article aims to review the scholarly literature on the intersection of International Human Resource Management (IHRM) and International Industrial Relations (IIR). Through a systematic literature review of the articles, the study identifies key themes, dominant theoretical perspectives, key findings, and existing research gaps. The results of the review provide a comprehensive synthesis of the current knowledge on how IHRM practices interact with IIR dynamics in the global business environment. The conclusion of the study highlights the theoretical and practical implications of the findings and suggests directions for future research.